Objective interpretation of dental disease in rabbits, guinea pigs and chinchillas - Boehmer, E.; Crossley, D. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2009)
Objective: Objective interpretation of dental disease in rabbits, guinea pigs and chinchillas with the use of anatomical reference lines. Material and methods: Skull radiographs (laterolateral and dorsoventral view) of 528 small mammals (204 rabbits, 151 guinea pigs and 173 chinchillas) were measured and analysed exactly in connection with a thorough intra- and extraoral clinical examination. 464 animals showed variable signs of malocclusion whereas 64 animals had a normocclusion. The clinical and radiographic changes of 224 individuals (52 rabbits, 41 guinea pigs and 131 chinchillas) were additionally compared with post mortem findings. Results: Particularly the comparison of the prepared skulls with the radiographs of the identical animals enabled the acquirement of species specific anatomical reference lines, that facilitate the objectice assessment of severity of dental disease in elodont species. Conclusion and clinical relevance: Using these reference lines the extent of malocclusion in rabbits, guinea pigs and chinchillas can be acquired more exactly and the results are reproducible by different examiners (staging). In addition to this these special lines facilitate to accurately monitor the progress of dental changes and thus to predict a probable long-term prognosis. The reference lines are absolutely applicable for daily use in practice.
Keywords: Malocclusion; normocclusion; radiography; assessment; long-term prognosis; staging